Add‐on peginterferon alfa‐2a to nucleos(t)ide analogue therapy for Caucasian patients with hepatitis B 'e' antigen‐negative chronic hepatitis B genotype D. Issue 1 (11th December 2018) - Lampertico, Pietro; Brunetto, Maurizia R.; Craxì, Antonio; Gaeta, Giovanni B.; Rizzetto, Mario; Rozzi, Antonella; Colombo, Massimo; ,
Summary: Nucleos(t)ide analogues (NAs) and peginterferon have complementary effects in chronic hepatitis B, but it is unclear whether combination therapy improves responses in genotype D‐infected patients. We conducted an open‐label study of peginterferon alfa‐2a 180 μg/wk added to ongoing NA therapy in hepatitis B e antigen (HBeAg)‐negative, genotype D‐infected patients with hepatitis B virus DNA <20 IU/mL. The primary endpoint was proportion of patients with ≥50% decline in serum HBsAg by the end of the 48‐week add‐on phase. Seventy patients received treatment, 11 were withdrawn at week 24 for no decrease in HBsAg, and 14 withdrew for other reasons. Response rate (per‐protocol population) was 67.4% (29/43) at week 48 (95% confidence interval [CI]: 51, 81) and 50.9% (28/55) at week 96 (95% CI: 38, 66). Median serum HBsAg decreased throughout peginterferon alfa‐2a treatment and was significantly lower than baseline at weeks 48, 72 and 96 ( P < 0.001). Decreases in HBsAg of ≥0.5‐log10 and ≥1‐log10 were documented in 19 (44.2%) and 6 (14.0%) patients at week 48 and 6 (10.9%) and 17 (30.9%) patients at week 96. The proportion of patients with HBsAg <1000, <500, <100 and <10 IU/mL at ≥1 timepoint during treatment was 78.6% (n = 44), 57.1% (n = 32), 21.4% (n = 12) and 7.1% (n = 4). Interferon gamma‐induced protein 10 increased from baseline up to week 48, with week 12 levels significantly associated with response at week 48. Addition of peginterferon alfa‐2a to ongoing NA therapy significantly decreased HBsAg levels in HBeAg‐negative patients with genotype D infection (ClinicalTrials.gov NCT01706575). Abstract : In this open‐label study in patients with genotype D, HBeAg‐negative chronic hepatitis B receiving nucleos(t)ide analogue therapy and with HBV DNA <20 IU/mL, peginterferon alfa‐2a add‐on therapy reduced HBsAg levels, with 29/43 (67.4%) patients having a >50% decline in HBsAg at week 48. An increase in Interferon gamma‐induced protein 10 from baseline up to week 48 was significantly associated with response.